PENINGKATAN MOTIVASI BELAJAR DAN KETERAMPILAN MENYIMAK MELALUI MODEL PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUAL, AND INTELLECTUAL) DALAM MENGIDENTIFIKASI UNSUR INTRINSIK CERITA PADA SISWA KELAS VI B SD NEGERI MOJOSONGO 5 KOTA SURAKARTA TAHUN 2025/2026 - Endah Puspita Sari; Dwi Bambang Putut Setiyadi; Tukiyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Peningkatan Motivasi Belajar dan Keterampilan Menyimak Melalui Model Pembelajaran SAVI (Somatic, Auditory, Visual, and Intellectual) dalam Mengidentifikasi Unsur Intrinsik Cerita pada Siswa Kelas VI B SD Negeri Mojosongo 5 Kota Surakarta Tahun 2025/2026. Master Program of Language Education. Widya Dharma University Klaten, 2026. The problems of this research were: 1) Can the SAVI (Somatic, Auditory, Visual, Intellectual) learning model improve the learning motivation of sixth grade students at SD Negeri Mojosongo 5 Surakarta?; 2) Can the SAVI learning model improve students’ listening skills in identifying the intrinsic elements of stories? The objectives of this research were: 1) To determine the improvement of students’ learning motivation through the implementation of the SAVI learning model; 2) To determine the improvement of students’ listening skills in identifying the intrinsic elements of stories through the implementation of the SAVI learning model for sixth grade students of SD Negeri Mojosongo 5 Surakarta in the academic year 2025/2026. This research used Classroom Action Research (CAR) with the Kemmis and McTaggart model consisting of planning, action, observation, and reflection stages. The research was conducted in two cycles. The subjects of this research were 28 students of class VI B at SD Negeri Mojosongo 5 Surakarta. The data were collected through observation, tests, questionnaires, interviews, and documentation. This research was conducted to determine the extent to which the implementation of the SAVI learning model assisted by folklore videos could improve students’ learning motivation and listening skills in identifying the intrinsic elements of stories. The results of the research showed that the implementation of the SAVI learning model was able to improve students’ learning motivation and listening skills. Students’ learning motivation increased from 40% in the pre-cycle to 71% in cycle I and increased to 88% in cycle II. The average score of students’ listening skills increased from 72 in the pre-cycle to 79 in cycle I and increased to 88 in cycle II. The percentage of learning completeness also increased from 35.7% in the pre-cycle to 85.7% in cycle I and reached 100% in cycle II. The SAVI learning model is very appropriate to be applied in Indonesian language learning because it involves students’ physical activities, auditory, visual observation, and intellectual activities in an integrated manner, making the learning process more active and meaningful.